Chemical Composition, Antioxidant and Antimicrobial Activities of Essential Oil from Leontopodium longifolium Ling. Issue 1 (2nd January 2018) - Qian, Han; Zhang, Wenhuan; He, Yilin; Li, Guoli; Shen, Tong
Abstract: The chemical composition of the essential oil obtained by hydro-distillation method from the aerial parts of Leontopodium longifolium Ling was analyzed by gas chromatography-mass spectrometry (GC-MS). Totally, forty-three compounds constituting 96.90 % of the oil were detected. The predominant constituents in the oil were α-bisabolol (28.37 %) and α-bisabolol oxide B (10.66 %). The essential oil showed relatively low antioxidant activity (IC50 = 8.907 mg/ml) in the 2, 2-diphenyl-1-picrylhydrazil (DPPH) radical scavenging assay, and showed weak antibacterial activity against Staphylococcus aureus, Bacillus subtilis and Pseudomonas aeruginosa with inhibition diameters from 11 mm to 13 mm in antimicrobial tests using disc agar diffusion method.